The Status of Implementing E-Learning Management System from the Point of View of Instructors of Blended Learning Courses at the University of Jordan - Nesreen Ali Almasri; Majed A. Abu Jaber (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This study aims at investigating the status of implementing e-learning management system from the point of view of instructors of blended learning courses at the University of Jordan. Methods: The population of the study consists of all instructors of blended learning courses from different academic ranks, for blended learning courses in scientific and humanities schools at the University of Jordan during the first semester of the academic year (2018/2019). The number of teachers who responded to the questionnaire were (34). A questionnaire consisting of 52 items was designed, and its items were distributed over four areas. Results: The results indicate that the status of implementing an e-learning management system from the point of view of instructors of blended learning courses at the University of Jordan was high with a mean of (4.35). The results also indicate that the difficulties facing instructors while using an e-learning management system for blended learning courses came to a moderate degree with a mean totaling (2.18) from the viewpoint of instructors. Moreover, the results show a statistically significant difference at (α = 0.05) due to academic rank in favor of instructors. Conclusions: The study recommends encouraging all faculty members at the University of Jordan to use blended learning to benefit from all the services provided by this method.